2016
DOI: 10.1016/j.yexmp.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FAT1 during the progression from DCIS to IDC and predict poor clinical outcome in breast cancer

Abstract: FAT1 and β-catenin are important tumor regulatory factors. The aim of this study was to detect the possible disparity in their expression from ductal carcinoma in situ (DCIS) to invasive ductal carcinoma (IDC) and to explore its correlation with clinicopathological factors. We used immunohistochemistry to detect protein expression of FAT1 and β-catenin in breast cancer tissues from 113 cases of DCIS and 149 cases of IDC. As compared with DCIS, expression of FAT1 and β-catenin were significantly decreased in ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Wang et al (107) used immunohistochemical analysis to detect FAT1 and β-catenin protein expression in ductal carcinoma in situ (DCIS) and IDC, revealing that, compared with in DCIS, the expression levels of FAT1 and β-catenin in IDC were significantly decreased. Additionally, loss of FAT1 expression was associated with higher histological grade and worse lymph node status in human breast cancer (107,108). In addition, FAT1 and β-catenin expression in DCIS and IDC were positively correlated with each other.…”
Section: Fat1 In Esccmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al (107) used immunohistochemical analysis to detect FAT1 and β-catenin protein expression in ductal carcinoma in situ (DCIS) and IDC, revealing that, compared with in DCIS, the expression levels of FAT1 and β-catenin in IDC were significantly decreased. Additionally, loss of FAT1 expression was associated with higher histological grade and worse lymph node status in human breast cancer (107,108). In addition, FAT1 and β-catenin expression in DCIS and IDC were positively correlated with each other.…”
Section: Fat1 In Esccmentioning
confidence: 99%
“…In addition, FAT1 and β-catenin expression in DCIS and IDC were positively correlated with each other. FAT1(-), β-catenin(-) or FAT1(-)/β-catenin(-) suggested a worse disease-free survival rate and prognosis in patients with breast cancer (107). The loss of FAT1 and β-catenin was associated with breast cancer progression, aggressive behavior and a poor prognosis, but the underlying mechanisms between the low expression levels of FAT1 in breast cancer and the Wnt/β-catenin signaling pathway are incompletely understood (107).…”
Section: Fat1 In Esccmentioning
confidence: 99%
See 2 more Smart Citations
“…identified FAT1 as a candidate tumor-suppressor gene which is able to suppress cancer cell growth by binding β-catenin and antagonizing its nuclear localization in glioblastoma (GBM) ( 8 ). Similarly, in breast cancer, it has been reported that the loss of FAT1 was associated with progression, aggressive behavior, poor prognosis, and cyclin-dependent kinase (CDK) 4/6 inhibitor resistance through the Hippo signaling pathway ( 9 , 10 ). The expression of FAT1, as the transcriptional target of E2F1, was frequently downregulated in ESCC tissues and inhibited proliferation, adhesion, and invasion through the MAPK signaling pathway ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%